2015
DOI: 10.1186/1471-2105-16-s19-s10
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies on molecular mechanisms of Nelfinavir resistance caused by non-active site mutation V77I in HIV-1 protease

Abstract: BackgroundThe human immunodeficiency virus (HIV-1) is a retrovirus causing acquired immunodeficiency syndrome (AIDS), which has become a serious problem across the world and has no cure reported to date. Human immunodeficiency virus (HIV-1) protease is an attractive target for antiviral treatment and a number of therapeutically useful inhibitors have been designed against it. The emergence of drug resistant mutants of HIV-1 poses a serious problem for conventional therapies that have been used so far. Until no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…Current studies of protease structures bearing different resistance mutations [7, 1820, 2733] are generally focussed on the protease flaps located above the protease active site and how the flaps mediate PI accessibility. Mutations in this area naturally affect the flap motions, reducing PI accessibility and binding.…”
Section: Introductionmentioning
confidence: 99%
“…Current studies of protease structures bearing different resistance mutations [7, 1820, 2733] are generally focussed on the protease flaps located above the protease active site and how the flaps mediate PI accessibility. Mutations in this area naturally affect the flap motions, reducing PI accessibility and binding.…”
Section: Introductionmentioning
confidence: 99%
“…An in silico structural study has shown that HIV-1 proteases containing the V77I substitution impact the cavity size of the protease active site and its binding affinity for nelfinavir. 22 Phenotypic experiments may be warranted to explore whether codon 77 is involved in darunavir susceptibility. It is surprising that the present analysis did not identify more positively selected darunavir resistance-associated sites, but this could reflect the rarity of emergent resistance to this agent.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using the DEER method concluded that the semi-open conformation is the most populated state, independent of the subtype [22,47], while NMR residual dipolar coupling (RDC) measurements suggested that the closed conformation was predominant [90]. However, all studies agree that the populations of these conformers change upon inhibitor binding, with the most potent inhibitors favoring the “closed” conformation [47,9193]. In all common subtypes of WT HIV-1 PR (subtypes B, C, and CRF_01 A/E), the residence time of inhibitors in the active-site pocket, and thus the inhibitory strength, is correlated with the degree to which said inhibitor induces flap closure.…”
Section: Case Studiesmentioning
confidence: 99%
“…For example, 13 out of the 19 hydrophobic core residues are associated with drug resistance acquisition, despite the absence of direct contacts with inhibitors [94]. Importantly, the accumulation of mutations in HIV-1 PR does not necessarily lead to increased drug resistance [48,93,99]. Indeed, alterations in inhibitor-protein interactions caused by secondary mutations correlate only partly with K i variations.…”
Section: Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation